IDENTIFYING STRATEGIES TO MAKE ASSESSMENT MORE FOOLPROOF AGAINST CHEATING AND PLAGIARISM IN THE AGE OF AI USING THE NOMINAL GROUP TECHNIQUE - Md Hamzaimi Azrol Md. Baharudin; Mohd Fakri Muda; Amminudin Ab Latif; Wan Zukri Wan Abdullah; Rasyad Afif Ibrahim (Journal of Islamic, Social, Economics and Development, 2023)
: Artificial intelligence (AI) is now widely utilized in a variety of industries, including education sector. Now more than ever, AI is being put to use in many fields, including the classroom. Nevertheless, it is anticipated that more challenges and impediments will arise in AI in the forthcoming years. One prominent concern pertains to an excessive dependence on AI, potentially resulting in issues such as academic dishonesty, intellectual theft, and insufficient educational development. Thus, the nominal group technique (NGT) was employed to present conclusions and recommendations from experts on managing academic dishonesty in the era of AI. The results of the study indicated that there are 14 strategies that can be used to make assignments more resistant to academic dishonesty in the age of AI. The findings of this study hold significance in generating numerous other strategies. Educators ought to explore new approaches to ensure assignments' continued relevance and efficacy in the era of artificial intelligence.